A study of packet scheduling with mobile cellular channel impairments - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Abdullah, Khaizuran (IEEE, 2012)
Long Term Evolution-Advanced (LTE-A) is a new radio access technology that is expected to provide better experience among the mobile cellular users. It delivers multimedia services using packet switching technology. Therefore, intelligent design of packet scheduling for the LTE-A to provide Quality of Service (QoS) comparable to fixed line services becomes crucial. However, packet scheduling over the LTE-A system faces a number of challenges. This paper studies a number of low complexity real time packet scheduling algorithms developed for the legacy mobile cellular systems. In addition to that, studies on performance impact due to mobile cellular channel impairments are presented. The study aims to identify the methods used by the existing packet scheduling algorithms as well to ascertain the performance degradations on the QoS of multimedia services due to the impact of the mobile cellular channel impairments. Future works include development of a new packet scheduling algorithm to overcome detrimental effects due to LTE-A channel impairments on the QoS of multimedia services.